HYPOKALEMIA – EARLY MARKER OF AUTOSOMAL RECESSIVE TUBULOPATHY (GYTELMAN’S SY) - CASE REPORT - Petrovic, Milica; Pilćević, Dejan; Violeta (Medicinski časopis, 2023)
Introduction: Hypokalemia is the most common feature of Gitelman’s syndrome, which is a rare, inherited, autosomal recessive kidney disease associated with tubule disease. Apart from hypokalemia, it is most often characterized by hypomagnesemia, metabolic alkalosis, hyperrenemic hyperaldosteronism, normal blood pressure, which can be lower, while the existence of arterial hypertension does not exclude the diagnosis of Gitelman’s syndrome. It affects men and women equally, approximately 1-10 cases per 40,000 population. The most common cause are mutations in the SLC12A3 gene that encodes the thiazide-sensitive sodium chloride cotransporter (NCCT) and the TRPM6 (cation channel subfamily 6 protein Claudin 16) gene that controls distal tubular magnesium transport. The aim is to present an adult patient with pronounced hypokalemia as part of Gitelman’s syndrome, which is not common in clinical practice. Case report: We present a 21-year-old man with severe hypokalemia as part of Gitelman’s syndrome. The disease manifested itself in non-specific complaints, and laboratory findings showed hypokalemia (2.0 mmol/L), which was the reason for urgent hospitalization. Through further examinations, the following were verified in the patient: hypomagnesemia, hypocalciuria, metabolic alkalosis, preserved kidney function and hypotension. Other, potential causes of hypokalemia are excluded by differential diagnosis. He was treated with potassium and magnesium replacement therapy, after which the symptoms disappeared and the electrolyte values improved. The diagnosis of Gitelman’s syndrome was made based on clinical and laboratory findings. A geneticist was also consulted. Conclusion: Hypokalemia as part of Gitelmann’s syndrome is rarely encountered in daily clinical practice. It is characterized by a variable clinical picture, with non-specific symptoms, the course and prognosis of which can significantly threaten the patient’s life. Timely diagnosis and application of adequate therapy require teamwork and experience of several specialists. Patients with symptoms should be treated symptomatically, and those without symptoms should be monitored 1-2 times a year.